PENDAMPINGAN PEMBUATAN BUKET UANG DAN SNACK DALAM MENINGKATKAN KUALITAS IQ RENDAH SUMBER DAYA MANUSIA DESA GALIS DAJAH KECAMATAN KONANG KABUPATEN BANGKALAN - Ahmad Wahyudi; Chozairi Chozairi; Waqiatus Zahroh (Universitas Al-Amien Prenduan, 2023)
Galis Dajah is one of the villages that has problems, especially in the quality of human resources, which are very minimal, including the people of Galis Dajah Village who do not take advantage of the potential that exists in the village, lack of water during the dry season, many people choose to leave the city to improve their economy compared to developing own village, and the declining mindset of students and even parents who think that working is more profitable than continuing their education to a higher level. This is a challenge for the group of real college participants to change the potential of the village with community service programs in the form of guiding children with low IQs and holding bouquet-making training. This program is carried out offline and field practice on the target object. in the program guiding children with low IQ, it is carried out with the method of slow reading repetition, in the bouquet-making training program it is carried out by direct practice methods with the community and students. The purpose of the program is to improve the community's ability and provide motivation for the achievement of quality human resources. The target in this activity is the community around the KKN location consisting of housewives, teenagers and children with low IQs.